If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 14b = 16b + 192 Reorder the terms: 14b = 192 + 16b Solving 14b = 192 + 16b Solving for variable 'b'. Move all terms containing b to the left, all other terms to the right. Add '-16b' to each side of the equation. 14b + -16b = 192 + 16b + -16b Combine like terms: 14b + -16b = -2b -2b = 192 + 16b + -16b Combine like terms: 16b + -16b = 0 -2b = 192 + 0 -2b = 192 Divide each side by '-2'. b = -96 Simplifying b = -96
| 42x^2+x=30 | | .833333=.66666w | | 7+2c-4(-4)=-9 | | 180+2.50x=1000 | | Y=x^2-14x+71 | | -30+19y=-30 | | 8(5-9)=10Q | | 3(2x+1)=4x-7 | | 6+3y=-12 | | 34.8=a+5.8 | | 0.375q=-.5 | | 6x-4(9-x)=106 | | 6x+1=97 | | 3=3y+8 | | 96=(4+x)x | | X+1=-1.5 | | 2+3x=50 | | 2x-6x+8=x-9+17 | | x+40=x | | x+12y+6x+3y= | | 5x+3=-4x-2q | | 10.5/-1.2= | | 6x-10=5x-20 | | -6n-20=-2n+4(1+3) | | 7t-4=8t-20 | | 4x+14-32=16x+8x-8 | | 2(b-21)=5b | | 5m-m+2=2m+10 | | -2x+3x-8=-3(-2x-1)+9 | | 3x-10=x+40 | | 5x+3=-4x-2q-3 | | -3-4(-46+7)=2(-46)-5(-46-3) |